Pancreas preservation: clinical practice and future developments. Issue 4 (August 2020) - Branchereau, Julien; Hunter, James; Friend, Peter; Ploeg, Rutger
Abstract : Purpose of review: To summarize recently published studies of preservation strategies including machine perfusion in pancreas transplantation. Recent findings: The shortage of conventional donors is leading units to use extended criteria donors (ECDs) and donors after cardiac death (DCD). Static cold storage (SCS) is still the standard method of preservation for pancreases and University of Wisconsin remains the gold standard preservation solution. In experimental studies, oxygen delivered during preservation reduced tissue injury and improved islet cell yield and function. Hypothermic machine perfusion of discarded human pancreases has been shown to improve adenosine triphosphate levels without adversely effect histology and oedema compared with SCS. Normothermic machine perfusion of discarded human organs has so far been challenging and led to increasing injury, rather than preservation. There are currently no clinical studies in pancreas transplant with the exception of a small number of pancreases being transplanted following normothermic regional perfusion. Summary: The storm of new organ preservation methods is now being more widely studied in the pancreas, with some promising results. These new strategies have the potential to allow expansion of the donor pool and greater utilization of ECD and DCD organs.